Nature based and technology based solutions for sustainable blue growth and climate change mitigation in marine biodiversity hotspots - Saleem Mustafa; Abentin Estim; Audrey Daning Tuzan; Chen Cheng Ann; Lim Leong Seng; Sitti Raehanah M. Shaleh (University of Warmia and Mazury, 2019)
This paper discusses the urgent need for human interventions in maximizing the promise of blue growth while ensuring sustainability in all its dimensions. It spares no efforts in highlighting the critical nexus between ocean conservation, climate change mitigation and the ecosystem services. The interpretation underscores the threat that unchecked deterioration of marine environment would present for health of the planet and its people. It is evident that the nature-based solutions provide the best options, but the significance of disruptive technologies and innovations cannot be underestimated. However, the decisions pertaining to devising and applying solutions should be informed by scientific reasoning and available evidence. Increasing attention given to blue economy shows the importance of exploring the sustainable solutions by shaping research that helps in identifying the tangible and integrated actions to fast track our progress towards implementing the Sustainable Development Goals.